2018
DOI: 10.1158/1535-7163.mct-17-1091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemical-Induced Mutational Load Increase on Immune Checkpoint Therapy in Poorly Responsive Murine Tumors

Abstract: A recurring historic finding in cancer drug development is encouraging antitumor effects observed in tumor-bearing mice that fail to translate into the clinic. An intriguing exception to this pattern is immune checkpoint therapy, as the sustained tumor regressions observed in subsets of cancer patients are rare in mice. Reasoning that this may be due in part to relatively low mutational loads of mouse tumors, we mutagenized transplantable mouse tumor cell lines EMT-6/P, B16F1, RENCA, CT26, and MC38 with methyl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 51 publications
4
21
0
Order By: Relevance
“…6a). PD-L1 blockade monotherapy had modest anti-tumor effects similar to results obtained previously and significantly extended survival 35 (Fig. 6b).…”
Section: Pd-l1 Blockade Does Not Increase Efficacy Of Ctx Therapy In supporting
confidence: 85%
See 1 more Smart Citation
“…6a). PD-L1 blockade monotherapy had modest anti-tumor effects similar to results obtained previously and significantly extended survival 35 (Fig. 6b).…”
Section: Pd-l1 Blockade Does Not Increase Efficacy Of Ctx Therapy In supporting
confidence: 85%
“…We have previously shown that PD-L1 blockade can have therapeutic effects in the EMT6-CDDP tumor model when treating both primary tumors and postsurgical metastatic disease in the neoadjuvant or adjuvant treatment settings 35,36 . Due to the findings of increased PD-L1 expression after CTX treatment, as well as CyTOF data suggesting that there was an increased infiltration of CD4 + and CD8 + T cells seen with CTX140 1q6d therapy, this model was used for testing whether any of the CTX regimens in combination with PD-L1 blockade could enhance overall therapeutic effects.…”
Section: Pd-l1 Blockade Does Not Increase Efficacy Of Ctx Therapy In mentioning
confidence: 99%
“…In the clinical setting, tumor burden at the start of treatment have an influence on the benefit from the treatment, with early treatment and smaller tumors being advantageous. 45,46 In keeping with this, we observed the expected augmented antitumor effect in a tumor model when inoculating a lower dose of CT26 cells for tumor growth ( Figure S3(a-c)). Furthermore, an earlier treatmentstarting as early as 8 days before tumor inoculationled to clearly better tumor inhibition ( Figure S3).…”
Section: Discussionsupporting
confidence: 75%
“…We therefore decided to evaluate whether combining the nintedanib and paclitaxel doublet with a PD-L1 immune checkpoint antibody could improve overall anti-tumor activity in the syngeneic immunocompetent EMT-6 and EMT-6/CDDP mouse tumor models. We observed that EMT-6/CDDP cells express higher levels of PD-L1 in vitro than the parental EMT-6 cells [79]. In this study, we found that the PD-L1 antibody treatment induced a similar tumor growth delay, with respect to the control groups, when treating either EMT-6 or EMT-6/CDDP primary tumors (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…We have found that EMT-6/CDDP cell line is more aggressive and metastatic, particularly to the lungs, compared to the parental cell line (unpublished observations). Also, we recently reported that this cell line expresses much higher levels of PD-L1 in vitro compared to the drug-sensitive parental cell line (EMT-6) [79].…”
Section: Resultsmentioning
confidence: 99%